Strong stability of weighted sums of NA random variables - Gan Shixin (International Journal of Mathematics and Mathematical Sciences)
We study the almost sure (strong) stability of weighted sums of NA random variables and obtain some new results which extend earlier results of Matula (1992), Chow and Teicher (1971), Jamison et al. (1965), and Petrov (1975).